Gender Differences in Weight-Related Attitudes and Behaviors Among Overweight and Obese Adults in the United States - Sandra A. Tsai MD, MPH; Nan Lv PhD; Lan Xiao PhD; Jun Ma MD, PhD (American Journal of Men's Health, 2016)
Few studies have used nationally representative data to focus specifically on gender differences in weight-related outcomes. This article examines gender differences in weight-related outcomes across the body mass index (BMI) spectrum in overweight and obese adults. Data from the National Health and Nutrition Examination Survey 2009–2010 was analyzed. Weight-related outcomes were accurate weight perception, weight dissatisfaction, attempted weight loss, successful weight loss, and weight loss strategies. Compared with women, overweight and obese men were less likely to have accurate weight perception (odds ratio [OR] = 0.36; 95% confidence interval [CI] = 0.30–0.44), weight dissatisfaction (OR = 0.39; 95% CI = 0.32–0.47), and attempted weight loss (OR = 0.55; 95% CI = 0.48–0.63). The modifying effect of gender on these associations decreased as BMI increased. By BMI 35, the mean probability of women and men to have accurate weight perception and weight dissatisfaction was 90%; attempted weight loss was 60% (women) and 50% (men). At lower BMIs, men had up to 40% less probability than women for these weight loss outcomes. Men who attempted weight loss were more likely than women to lose and maintain ≥10 lb over 1 year (OR = 1.41; 95% CI = 1.20–1.65) and increase exercise and eat less fat as weight loss strategies; women were more likely to join weight loss programs, take prescription diet pills, and follow special diets. A need exists for male-specific interventions to improve overweight and obese men’s likelihood for accurate weight perception, attempted weight loss, and ultimately, successful weight loss.